Environmental certification of building materials in Slovak Republic - Eštoková, A. (Видавництво Національного університету "Львівська політехніка", 2008)
Each building and building material directly or indirectly interact with the environment and may cause pollution or deplete our natural resources. The eco-labelling process seems to be a very effective mechanism to promote building products that have a lesser impact on the environment. The review of building materials environmental certification in Slovak republic is presented in this paper. Кожна будівля і будівельні матеріали так чи інакше взаємодіють з навколишнім середовищем і є причиною забруднення та погіршення природного середовища. Екологічне маркування є ефективним механізмом забезпечення спорудження будівель, що матимуть найменший негативний вплив на природу. У цій роботі подано огляд будівельних матеріалів для сертифікаціїї у Словаччині.